Evaluasi Sistem Pengamanan Kantor Kepolisian Negara Republik Indonesia: Studi Kasus Sistem Pengamanan di Polsek X - Rahmatia, Liswinda Zafirah; Sapto Priyanto; Muhamad Syauqillah; Imam Subandi (Universitas Ekasakti, 2024)
In Indonesia, acts of terrorism that attack police officers and police facilities, it can be understood that terrorist groups actually do this because of feelings of revenge and also the motive that the authorities no longer have the trust of the community that they can provide security and maintain the peace of the country's life. Several cases that have occurred in Indonesia include the attack on the Headquarters of the Indonesian National Police on March 31, 2021 and the suicide bombing that occurred at the Astana Anyar Police Station on December 7, 2022. These two tragedies are clear examples of the urgency of increasing security at police stations. Things that make terrorist attacks on police facilities and officers can be described based on the existence of exposed, vital, iconic, legitimate, destructible, occupied, near, and easy. The success of an act of terrorism depends on several factors, including the terrorist group's ability to plan and execute an attack effectively, as well as security weaknesses at the target of the attack. To overcome this problem, it is necessary to improve the security system by applying the concept of Crime Prevention Through Environmental Design (CPTED) to prevent similar attacks in the future.